Entre o formulado nos planos e a visão dos docentes: formação, profissão e valorização docente na rede pública municipal de educação em Bela Vista de Goiás - Guimarães Neto, Altamiro Gomes (2018)
This work is connected to the line of research entitled State, Policies and History of Education of the Postgraduate Program in Education of the Faculty of Education/UFG. Its theme, which is set out in the title, Between the formulated in the Plans and the teachers' views: Formation, Profession and Teachers’ Valorization in the Municipal Public Education System in Bela Vista de Goiás, articulates pertinent questions in the areas of legislation, management, politics and formation of teachers of Basic Education, more specifically, at the municipal level. This research seeks to analyze, know, understand and reflect on the formation, profession and teachers’ valorization in the Municipal Public Education System of Bela Vista de Goiás. The investigation was carried out through procedures that consisted of a wide review of the literature in the area, documentary research in institutions such as the headquarter of the City Hall and the Municipal Secretariat for Education and Culture of Bela Vista de Goiás as well as in official documents of the Federal Government/MEC. The theoretical and conceptual framework of the research, especially in relation to the problems of education plans, educational planning, formation, profession and valorization considered and dialogued with authors who contributed critically to the understanding of these aspects and their relations in the most recent context of the Brazilian Education. In addition, questionnaires were applied to teachers and trade unions that are part of the municipality researched and the answers were categorized and analyzed detecting the existence of constitutive aspects inherent to the profession, such as: deficient professional qualifications, low remuneration, precariousness, silence, teacher malaise and absence of trade union awareness. The results of the research showed that most teachers recognize the importance of the initial and continued teacher education and claim the need for change in the national education policy. The research evidenced that the continued formation is fundamental in the process of professional development providing new reflections on both the action of the teacher and new teaching means so that teachers can develop their pedagogical work and, consequently, be valued. However, this process should be linked to the improvement of working conditions and teachers’ valorization taking into consideration the quality of the teaching-learning process. It is necessary, in this direction, to resize the policy of initial and continued formation and teachers’ valorization as a democratic process through which teachers collectively seek autonomy in producing knowledge and values, taking into account the school context in which the pedagogical practice takes place. Thus, even considering the uncertainties and challenges of the current context, considering what comes in the education plans and the educational reality that imposes limits to the management of municipal education and interferes in the management and teaching practices, we understand that the teachers play a fundamental role in the construction of a quality school. For this reason, we also understand that it is necessary to ensure that the teaching profession is built on an initial and continued quality formation, in an articulated way to the teachers’ valorization and the construction of the dignity of the profession, mainly in the municipal and state spheres, responsible for the provision of Basic Education in its almost totality.